DEVELOPING THE CONDITIONS FOR DATA DRIVEN CHANGE TO IMPACT STUDENT ACHIEVEMENT AND BUILD TEACHER CAPACITY - Madden, Jake (PEOPLE: International Journal of Social Sciences, 2019)
Schools have been caught up in responding to the calls of external accountability. This has challenged school leaders to establish data gathering practices that ultimately lend themselves to creating school wide instructional systems to impact teaching and learning and offer a consistent instructional approach. This paper outlines how one school established a data driven approach to improve teacher performance by focusing on key elements using a literature focused approach as a catalyst for driving new innovation. The paper considers how a data driven focus (DDF) allows leaders to intentionally and systematically improve student learning. The paper begins by unpacking the new focus on instructional leadership. It unveils how leaders are required to create the foundation to develop a DDF as a vehicle to facilitate information about student achievement within the school. The second part of the paper reports on the change process used to implement DDF as guided by key elements. It entails a 6-step cycle involving 1) developing a desire for change, 2) reflection on data, 3) aligning school programs & curricula, 4) Understanding by Design instructional practices and professional development, 5) provision of feedback, and 6) nurturing teacher implementation. It reviews how one school, through the focus of improving instruction and intentionally using key literature-based concepts, developed a raised awareness for using curriculum and assessment data to guide decision making. This paper provides a rich example of how a school can facilitate and sustain a data-based decision-making culture in schools. The paper concludes that being a data-focused school is a possibility for each and every school.